DISCIPLINE AND RESPONSIBILITIES CHARACTERS OF SENIOR HIGH SCHOOL(SMA) STUDENTS THROUGH PROBLEM BASED LEARNING ON TRANSPORT SYSTEM MATERIAL - Nafisah Hanim; Irda Risna; Auriza Satria Putri (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2022)
The research aimed to know the development of discipline and responsibility character ofthe students at SMA Negeri 1 Suka Makmur Nagan Raya in biology subject on transport system concept through a problem based learning model. This research used descriptive qualitative method. The samples were students of class XI. Character values obtained from observations using a questionnaire instrument. Data were analyzed using the percentage formula. The result showed that there was a student's character development at each meeting, namely the value of discipline character at the first meeting with a percentage of 65 increased to 88 at the second meeting while the value of responsibility character at the first meeting with a percentage of 63 increased to 90 at the second meeting. It can be concluded that the problem based learning model can increase the value of discipline and responsibility character of the students at SMA Negeri 1 Suka Makmur Nagan Raya.